Exosomes - breakthrough in the regenerative medicine and a way to improve the quality of the life - Anna Brzozowska; Monika Maj-Dziedzic; Marcelina Sikora; Marta Zarzycka; Ines Plewniok; Jeremiasz Dubiel; Adrian Maj; Martyna Warno; Wiktor Kozik; Greta Śmietana (Kazimierz Wielki University, 2024)
Introduction Exosomes are small, membrane-bound extracellular vesicles that play a pivotal role in intercellular communication. Exosomes have garnered significant interest in regenerative medicine due to their unique properties that support tissue repair, regeneration, and healing. These extracellular vesicles play a crucial role in intercellular communication, and their regenerative potential makes them promising tools in the field of regenerative medicine.    Purpose of the study This review aims to present the regenerative properties of exosomes and their clinical applications in many fields of medicine. The main aim is to present exosomes as a substance that restores health, youth and vitality.    Material and method Literature review was primarily based on scientific materials, English and Polish databases and original research. The following English keywords and its Polish equivalents were used to search Google Scholar and PubMed: " exosomes", "regenerative medicine", "stem cells".